The involvement of José de la Riva Agüero y Sánchez Boquete in the independence process of Peru, as seen through his memoirs - San Martín Vásquez, Juan Alberto (2020)
In his memoirs, written when he had left Peru and had retired from public service, José de la Riva Agüero y Sánchez Boquete, using the pseudonym “Pruvonena”, analyzed his political involvement in the process of Peruvian independence, in which he actively opposed Congress, accusing its members of being demagogues and of handing absolute power to Simón Bolívar and to the troops of Gran Colombia in the struggle to defeat Spanish forces, which he considered an affront to the national army, since it entailed the subordination of Peruvian officers. The attitude of Riva Agüero, as reflected in his political activities, in which he made several errors that resulted in his removal as president, is defended in his memoirs, which offer an insight into the weakened and anarchic condition of the nascent Peruvian state during the early years of the republic.